Pendampingan Pengolahan Ikan Gatul sebagai Sumber Ekonomi Keluarga bagi Ibu-Ibu Rumah Tangga di Desa Tanggul Rejo Manyar Gresik - Miftachul Ulum; Nashihin Nashihin; Abdullah Zawawi; Hisbulloh Huda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2021)
Each area of ​​an area always has enormous potential assets, as well as the Tanggul Rejo Manyar Gresik village. In fact, every asset owned by a region has not been fully utilized. Assistance activities in the village of Tanggul Rejo with the utilization of gatul fish which have been neglected so far have become a potential that can make an economic source for the surrounding community and even become an economic chain for the community as a whole. The Asset Base Community Development approach or better known as the ABCD method in embedding hidden assets makes changes in the social order and even the economic order for the better. Assistance for housewives in Tanggul Rejo village has created the use of economic resources which can make an alternative source of gatul fish management more useful through the introduction and disclosure of hidden assets. The disclosure of hidden assets in the Discussion Group Forum appreciates the success dreams that have been experienced by the people of Tanggul Rejo Manyar Gresik village will become a reality through the disclosure of successes that have been experienced by the community before.